Urinary density measurement and analysis methods in neonatal unit care - Maria Vera Lúcia Moreira Leitão Cardoso; Gabrielle Gama Teixeira Lima; Leiliane Martins Farias (Universidade Federal do Ceará, 2013)
The objective was to assess urine collection methods through cotton in contact with genitalia and urinary collector to measure urinary density in newborns. This is a quantitative intervention study carried out in a neonatal unit of Fortaleza-CE, Brazil, in 2010. The sample consisted of 61 newborns randomly chosen to compose the study group. Most neonates were full term (31/50.8%) males (33/54%). Data on urinary density measurement through the methods of cotton and collector presented statistically significant differences (p<0.05). The analysis of interquartile ranges between subgroups resulted in statistical differences between urinary collector/reagent strip (1005) and cotton/reagent strip (1010), however there was no difference between urinary collector/ refractometer (1008) and cotton/ refractometer. Therefore, further research should be conducted with larger sampling using methods investigated in this study and whenever possible, comparing urine density values to laboratory tests.